Археологические свидетельства производственной деятельности как поисковые признаки месторождений полезных ископаемых - Шубин, Ю.П. (Наукові праці УкрНДМІ НАН України, 2014)
Stages of ancient mining-metallurgical activities and geological methods of their solutions have been examined. Specifications of sepa-rate stages of productive activities have revealed current problems, methods for solving problems, and the importance of finding in the search for mineral exploration. Розглянуті етапи стародавньої гірничо-металургійної дія-льності і геологічні методи їх вирішення. Деталізація окремих етапів виробничої діяльності виявила суттєві проблеми, методи їх вирішення і значення отриманих даних для пошуків родовищ корисних копалин.
Remove selected